Intellectual Debates in Relation to the Opening of the Bolgar Islamic Academy (Tatarstan, Russian Federation, 2017) - Almazova, Leila Ildusovna; Shamsutov, Rustem Ilshatovich (International Journal of Criminology and Sociology, 2022)
The Bolgar Islamic Academy (BIA) was conceived as the highest level of religious education, where Muslims from all Russian Federation could get MA and PhD degrees in Islamic Studies. Among the main tasks initially set for this educational institution was: a) Integration of all levels of Islamic education into educational consistency throughout the Russian Federation; b) Protection of Muslims from foreign influence c) Development of Russian national traditions in the sphere of Islamic theology; d) Providing opportunities for Russian Muslims to receive high-quality Islamic education (on the Arabic language) in their homeland. On September 4, 2017, the Bolgar Islamic Academy opened its doors for 75 students. Its opening was preceded by a rather interesting discussion, which affected wide audience, including Muslims, Christians, secular-oriented individuals and academic community. On the early organizational stage three concepts of the Bolgar Islamic Academy have developed: 1) the concept of the Muslim Spiritual Council of Republic of Tatarstan, 2) the project of the academic community (by Alfrid Bustanov), and 3) the proposal of Muslim activist Rezeda Safiullina. There were also heated debates between supporters of traditional madrasa education and reformist wing on the pages of the popular electronic newspaper Business Online. The discussion, debates and the final choice of the concept are a wonderful illustration of the Talal Assad’s concept of orthodoxy, which is nothing more than a “distinctive relationship - a relationship of power”.